Perancangan Motif Tekstil dengan Mengolah Karya Lukis Anak Down Syndrome - Ajeng Annisa Faradhila; Setyawan . (JURNAL RUPA, 2020)
The motif-designing collaborates the painting of Dwi Andini Ma'ruf (23 year-old), a student who experienced mosaic down syndrome 15% with textile design based on characters in the form of sloppy lines and imperfect shapes. The designing-process uses a design approach that goes through three main processes, namely; exploration, termination and extraction processes. By using this approach, the researcher explores information related to down syndrome, plans the designing-activity related to the concept as a whole, and analyzes the design that has been made to draw conclusions and solve existing problems. The result of the designing process is textile motifs that reprocess the painting of a down syndrome person’s painting as an initial idea by maintaining a composition in accordance with the character of the subject and is interpreted through a simple design using the screen printing technique for ready-to-wear clothing. The line emphasis and color selection are displayed in full to accentuate the uniqueness of the subject's perspective.